Causal effects of specific gut microbiota on bone mineral density: a two-sample Mendelian randomization study - Chen, Shuai; Zhou, Guowei; Han, Huawei; Jin, Jie; Li, Zhiwei (Frontiers in Endocrinology, 2023)
Background Recent studies have reported that the gut microbiota is essential for preventing and delaying the progression of osteoporosis. Nonetheless, the causal relationship between the gut microbiota and the risk of osteoporosis has not been fully revealed. Methods A two-sample Mendelian randomization (MR) analysis based on a large-scale genome-wide association study (GWAS) was conducted to investigate the causal relationship between the gut microbiota and bone mineral density (BMD). Instrumental variables for 211 gut microbiota taxa were obtained from the available GWAS meta-analysis (n = 18,340) conducted by the MiBioGen consortium. The summary-level data for BMD were from the Genetic Factors for Osteoporosis (GEFOS) Consortium, which involved a total of 32,735 individuals of European ancestry. The inverse variance-weighted (IVW) method was performed as a primary analysis to estimate the causal effect, and the robustness of the results was tested via sensitivity analyses by using multiple methods. Finally, a reverse MR analysis was applied to evaluate reverse causality. Results According to the IVW method, we found that nine, six, and eight genetically predicted gut microbiota were associated with lumbar spine (LS) BMD, forearm (FA) BMD, and femoral neck (FN) BMD, respectively. Among them, the higher genetically predicted Genus Prevotella9 level was correlated with increased LS-BMD [β = 0.125, 95% confidence interval (CI): 0.050–0.200, P = 0.001] and FA-BMD (β = 0.129, 95% CI: 0.007–0.251, P = 0.039). The higher level of genetically predicted Family Prevotellaceae was associated with increased FA-BMD (β = 0.154, 95% CI: 0.020–0.288, P = 0.025) and FN-BMD (β = 0.080, 95% CI: 0.015–0.145, P = 0.016). Consistent directional effects for all analyses were observed in both the MR-Egger and weighted median methods. Subsequently, sensitivity analyses revealed no heterogeneity, directional pleiotropy, or outliers for the causal effect of specific gut microbiota on BMD (P > 0.05). In reverse MR analysis, there was no evidence of reverse causality between LS-BMD, FA-BMD, and FN-BMD and gut microbiota (P > 0.05). Conclusion Genetic evidence suggested a causal relationship between the gut microbiota and BMD and identified specific bacterial taxa that regulate bone mass variation. Further exploration of the potential microbiota-related mechanisms of bone metabolism might provide new approaches for the prevention and treatment of osteoporosis.